0072 Preclinical Characterization of SUVN-G3031, a Histamine H3 Receptor Inverse Agonist for the Treatment of Narcolepsy. (27th May 2020) - Jayarajan, P; Subramanian, R; Kamuju, V; Muddana, N; Palacharla, R; Mekala, V; Abraham, R; Reballi, V; Achanta, P; Nirogi, R
Abstract: Introduction: Narcolepsy is a chronic sleep disorder characterized by overwhelming daytime drowsiness, sudden attacks of sleep and sometimes accompanied by cataplexy. Although the orexin deficiency is considered to be the primary cause of this disorder, lot of attention has been focused recently on targeting histaminergic neurotransmission by blockade of histamine H3 receptor (H3R). SUVN-G3031 is one of the potent and selective H3R inverse agonist currently being evaluated in a Phase 2 study as monotherapy for the treatment of narcolepsy with and without cataplexy (ClinicalTrials.gov Identifier: NCT04072380). Methods: Binding of SUVN-G3031 in human and rat histamine H3R was evaluated in in vitro radioligand binding assay and functionality was assessed in GTPγS assay. Pharmacokinetic properties were evaluated after oral administration in rat and dog. Neurotransmitters like histamine, dopamine and norepinephrine were estimated in rat cortex using microdialysis. Results: SUVN-G3031 is an inverse agonist at histamine H3R with hKi of 8.7 nM and showed minimal binding against over 70 target sites. SUVN-G3031 exhibited desired pharmacokinetic properties in rat and dog with excellent brain penetration in rats. SUVN-G3031 produced significant increase in histamine, dopamine and norepinephrine levels in cortex. SUVN-G3031 produced no change in the striatal and accumbal dopamine levels in rats, suggesting no propensity to induce abuse liability. SUVN-G3031 blocked R-α-methylhistamine induced water intake and produced dose dependent increase in tele -methylhistamine levels in various brain regions and in cerebrospinal fluid of male Wistar rats. Conclusion: SUVN-G3031 is an inverse agonist at histamine H3 receptor and results from the preclinical studies presented here provide a strong evidence for the potential utility of SUVN-G3031 in the treatment of narcolepsy with and without cataplexy. Support: None